Assessing the influence of migraine on the prognosis of ischemic stroke: a prospective cohort study - Oliveira, Felipe Araújo Andrade de; Dourado Filho, Mario Genuíno; Rocha-Filho, Pedro Augusto Sampaio (Headache Medicine, 2022)
Abstract Introduction There is controversy as to whether migraine implies a poorer prognosis after the stroke. Objectives To assess whether migraine implies a poorer prognosis after the stroke. Methods This was a prospective cohort study carried out in a hospital in the city of Recife, Pernambuco, Brazil. We included consecutively hospitalized patients with ischemic stroke within 72 hours of symptom onset. A diagnosis of ischemic stroke was made by the presence of a diffusion restriction pattern on the MRI within a compatible clinical context. Patients were assessed by a neurologist who conducted an interview using a semi-structured questionnaire containing questions regarding sociodemographic data, the presence and characteristics of headaches in their lives and the related clinical condition to ischemic stroke. The headaches presented were classified according to the diagnostic criteria of the third edition of the International Classification of Headache Disorders. The National Institute of Health Stroke Scale and the modified Rankin scale were used. Patients underwent MRI of the brain with diffusion and with perfusion. Patients were assessed by telephone 3 months after the stroke to determine the prognosis. Results A total of 221 patients were included, 59.3% of whom were male, and a mean age of 68.2 ± 13.8 years. One hundred and seventy-eight patients (178/221; 81%) were assessed 3 months after the ischemic stroke. Migraine was not associated with the stroke prognosis (logistic regression). Conclusion Migraine is not associated with the prognosis of ischemic stroke. Key-Words: Cerebrovascular Disease, Ischemic Stroke, Migraine, Stroke outcome.